Pharmacokinetics and non-analgesic effects of S- and R-ketamines in healthy volunteers with normal and reduced metabolic capacity - Persson, J.; Hasselström, J.; Maurset, A.; Öye, I.; Svensson, J.-O.; Almqvist, O.; Scheinin, H.; Gustafsson, L. (European journal of clinical pharmacology, 2002)
There is a growing interest in low-dose ketamine as an analgesic agent in different intractable pain conditions. Due to its narrow therapeutic window, well-defined pharmacokinetic parameters are essential for its successful use in these situations. Arterial data for ketamine or its enantiomers have not been reported before. The metabolic pathways involved in the metabolism of S- and R-ketamines are not known. Ten healthy male volunteers received 7 mg infusions of R- and S-ketamine-hydrochloride in a randomised order over 30 min on 2 separate days. Six were extensive metabolisers, two were poor metabolisers of debrisoquine (CYP2D6) and two were poor metabolisers of mephenytoin (CYP2C19). Arterial and venous concentrations and non-analgesic side effects were measured. Subjective side effects were mild but more pronounced for S- than for R-ketamine. There were no salient differences between the subjects with reduced and normal metabolic capacity in pharmacokinetic parameters or in side effects. Volumes of distribution and mean residence times were 40% smaller for arterial than for venous data. The mean clearance of R-ketamine, 0.020 l min(-1) kg(-1), was slightly but significantly lower than of S-ketamine, 0.024 l min(-1) kg(-1). There are large differences between arterial and venous data in the pharmacokinetic parameters that are heavily dependent on distribution processes. Parameters mainly reflecting elimination, such as clearance and area under the concentration time curve, are unchanged. The choice of sampling site could be important when computer-controlled infusions are used.